Realising Person-Centredness: Transitioning to a Clustered Domestic Model of Aged Residential Care for People with and without Dementia - Shannon, Kay; Cook, Catherine; Neville, Stephen (Wiley, 2024)
Introduction Many older people who cannot live independently live in aged residential care facilities to obtain support with social and healthcare needs. Despite old age being a precious time for people to live well, many facility residents have limited access to activities that promote their well-being and connectedness. In New Zealand, one provider of aged residential care developed a village inspired by de Hogeweyk in the Netherlands, where resident engagement in valued activities supports continuing lifelong identities. Methods The study aimed to explain the transition from a traditional Aged Residential Care facility to a clustered domestic model of care. A critical realist theoretical perspective underpinned case study research. Data comprised transcripts of interviews with key informants, facility staff, residents and their families, records of observation of residents' daily lives, organisational documents, photographs and the first author's study journal. Results The intersection of philosophical workplace change to support delivery of person-centred care and a change in the physical environment enabled realisation of the organisational vision of residents living normal lives. Conclusion Policy makers and practitioners must be aware that while a domestic-scale environment provides cues to normal living, staff who know residents and what is important to them enable participation in community and valued activities. Implications for Practice Innovative living arrangements are a synthesis of philosophical aspirations, architectural and design vision, dedicated leadership and committed teamwork.
Keywords: 1110 Nursing; 3901 Curriculum and pedagogy; 4205 Nursing